The newspaper man of Sentul - Seng-Guan, Yeoh ([Kuala Lumpur Publisher not identified], 2014)
Sentul is a colonial era railway township in Kuala Lumpur being transformed by urban re-development and gentrification in the past decade. Born and bred in Sentul, Joseph has been delivering newspapers to the locality for over 30 years. This is the only job he has known. This documentary provides a glimpse into his work routines, memories of Sentul and passion for Hollywood movies.
Keywords: Work -- Newspaperman